Marist values that students of higher education perceive in the teacher. - Lopez Herrera, Vicente Gerardo (2019)
Nowadays, schools speak a lot about comprehensive training in human being, these philosophies are based on humanistic concepts. Although, they move away from the institutional management and traditional teaching values.   This article shows that is possible a humanized and humanizing context inside the university through the systematization of experiences provided by Marcelino’s followers, who continuously search for new possibilities in order to accomplish Marist Mission.  They have as inspiration source the dream from the founder: “living the Catholic Gospel with concrete circumstances of each historical context”.